2015
DOI: 10.2459/jcm.0b013e328365c325
|View full text |Cite
|
Sign up to set email alerts
|

Changed outcomes of fetuses with congenital heart disease

Abstract: Our data show a reduced overall and surgical mortality, with respect to our previous study, resulting from resulting from an improved perinatal management and treatment of affected fetuses in the more recent era.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…In this contemporary, multicenter cohort of fetuses with EA/TVD, the perinatal mortality was 45%, substantially higher than other forms of congenital heart disease in the current era. 14,15 However, in comparison with previous single-center series of EA/TVD over the past several decades, a greater proportion of fetuses survived to birth. This may be attributable to a combination of factors, including a lower rate of pregnancy termination and progress in prenatal diagnosis resulting in greater likelihood of identifying less severely affected fetuses.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…In this contemporary, multicenter cohort of fetuses with EA/TVD, the perinatal mortality was 45%, substantially higher than other forms of congenital heart disease in the current era. 14,15 However, in comparison with previous single-center series of EA/TVD over the past several decades, a greater proportion of fetuses survived to birth. This may be attributable to a combination of factors, including a lower rate of pregnancy termination and progress in prenatal diagnosis resulting in greater likelihood of identifying less severely affected fetuses.…”
Section: Discussionmentioning
confidence: 91%
“…The overall perinatal outcome for the 243 fetuses is depicted in Figure 1. There were 15 known pregnancy terminations, all but 1 of which occurred at less than 24 weeks GA (median, 21 weeks GA [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31]). There were 41 fetal demises, and the median GA at demise was 30 weeks (22-37).…”
Section: Resultsmentioning
confidence: 99%
“…This is well correlated with a previous Italian multicentric study that reported an overall TOP rate of 20%. 23…”
Section: Principal Findingmentioning
confidence: 99%
“…Perinatal mortality (defined as fetal demise or death before neonatal discharge) remains high among fetuses diagnosed with Ebstein's anomaly; there are reports of up to 45% in recent large multicentre cohort series of fetuses with Ebstein's anomaly or tricuspid valve dysplasia, substantially higher than other forms of congenital heart disease in the current era [8,9]. In the fetus, severe tricuspid regurgitation may lead to cardiomegaly, hydrops, and arrythmia, with demise rates as high as 48% [10].…”
Section: Introductionmentioning
confidence: 99%